Clinical Implications and Hospital Outcome of Immune‐Mediated Myositis in Horses. (2nd January 2017) - Hunyadi, L.; Sundman, E.A.; Kass, P.H.; Williams, D.C.; Aleman, M.
Abstract : Background: Immune‐mediated myositis (IMM) is a cause of rhabdomyolysis, stiffness, and muscle atrophy predominantly affecting Quarter horses. Limited information is available with regard to outcome, prognostic indicators, and associations with concurrent diseases. Hypothesis/Objectives: To report outcomes and associations between outcome and clinical and laboratory parameters, and presence of concurrent illness. Animals: Sixty‐eight horses; 52 Quarter horses and related breeds and 16 other breeds. Methods: Retrospective cohort study (1991–2014). Medical records of horses with histological diagnosis of IMM were reviewed. Data recovery included signalment, laboratory variables, therapy, and outcome. Logistic regression was used to quantify the association between potential prognostic factors and survival to discharge. Results: Quarter horses were younger (mean < 4 years, range 3 months–21 years) than other breeds (mean < 10 years, range 1–23 years). Pathogens causing concurrent or recent infection included S. equi equi, S. equi zooepidemicus, C. pseudotuberculosis, Anaplasma phagocytophilum, herpes virus‐1, and influenza. The most common clinical signs consisted of rapidly progressive diffuse symmetrical muscle atrophy (80%), stiff gait (74%), and fever (44%). All horses that received medical therapy immediately upon admission survived to discharge (survival proportion = 87%). Leucocytosis was a common finding (60%). Horses with concurrent fever and other illness had a poor prognosis for hospital discharge. Conclusions and Clinical Importance: Horses with IMM can have a favorable outcome. Horses with concurrent fever and another illness had decreased probability of survival to discharge.